Contribuição da polinização entomófila para a produção de frutos de aceroleira - Oliveira, José Eduardo Martins De; Nicodemo, Daniel; Oliveira, Favízia Freitas De (Escola de Agronomia/UFG, 2015)
The production of West Indian cherry may increase considerably when its flowers are visited by bees. This study aimed to determine the dependence degree of the West Indian cherry Olivier cultivar, concerning the entomophilous pollination, as well as discovering its potential pollinators, by studying its floral characteristics and the behavior of visiting insects. The most common insects were: Centris (Centris) varia (43.9 %), Centris (Centris) decolorata (17.4 %), Centris (Centris) flavifrons (15.6 %), Epicharis (Epicharana) flava (7.6 %), Centris (Centris) nitens(5.9 %), Centris (Hemisiella) tarsata (4.9 %), Tetragonisca angustula (2.5 %) and Trigona spinipes (2.3 %). It was observed that bees from the Centris and Epicharisgenera collected oil, while the T. angustula bees collected pollen and the T. spinipes bees cut the flowers. Fructification was higher when the flowers were open to pollination (27 % of fruit production), followed by manual cross pollination (11 %) and restricted pollination (1 %). No fruits were obtained through self-pollination. The Olivier cultivar was highly dependent on entomophilous pollination and the Centris and E. flava bees can perform this service efficiently.

A produção de acerola pode aumentar consideravelmente, quando suas flores são visitadas por abelhas. Este estudo objetivou determinar o grau de dependência da aceroleira cultivar Olivier, em relação à polinização entomófila, bem como conhecer seus polinizadores potenciais, por meio de análise das características florais e do comportamento da entomofauna visitante. Os insetos mais frequentes foram: Centris (Centris) varia (43,9 %), Centris (Centris) decolorata (17,4 %), Centris(Centris) flavifrons (15,6 %), Epicharis (Epicharana) flava (7,6 %), Centris (Centris) nitens (5,9 %), Centris (Hemisiella) tarsata (4,9 %), Tetragonisca angustula (2,5 %) e Trigona spinipes (2,3 %). Foi observado que as abelhas dos gêneros Centris e Epicharis coletaram óleo, enquanto as T. angustula coletaram pólen e as T. spinipes cortaram as flores. A frutificação foi maior quando as flores estavam abertas à polinização (27 % de frutos gerados), seguida de polinização manual cruzada (11 %) e polinização restrita (1 %). Não houve formação de frutos por meio de autopolinização. A cultivar Oliver demonstrou alta dependência da polinização entomófila, sendo que abelhas Centris e E. flavapodem realizar tal serviço eficientemente.
Contribution of entomophilous pollination to fruit production of West Indian cherry plants
Keywords: Malpighia emarginata DC. Malpighiaceae; fructification; pollination; Malpighia emarginata DC. Malpighiaceae; frutificação; polinização